2021
DOI: 10.7150/thno.59759
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage targeted theranostic strategy for accurate detection and rapid stabilization of the inflamed high-risk plaque

Abstract: Rationale: Inflammation plays a pivotal role in the pathogenesis of the acute coronary syndrome. Detecting plaques with high inflammatory activity and specifically treating those lesions can be crucial to prevent life-threatening cardiovascular events. Methods: Here, we developed a macrophage mannose receptor (MMR)-targeted theranostic nanodrug (mannose-polyethylene glycol-glycol chitosan-deoxycholic acid-cyanine 7-lobeglitazone; MMR-Lobe-Cy) designed to identify inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Therefore, macrophages have been considered a promising target for detection and identification of the atherosclerotic lesions. Some signal receptors, including transmembrane proteins (CD47, CD36, CD44, CD68), a mannose receptor (MMR), folate receptor beta (FR-β), a collagenous structure (MARCO), and transferrin receptor 1 (TfR1), are found to be overexpressed on the surface of macrophages, which have been employed as biological targets for imaging macrophages in atherosclerotic plaques.…”
Section: Targeted Imaging Of Activated Cells In Atherosclerosismentioning
confidence: 99%
“…Therefore, macrophages have been considered a promising target for detection and identification of the atherosclerotic lesions. Some signal receptors, including transmembrane proteins (CD47, CD36, CD44, CD68), a mannose receptor (MMR), folate receptor beta (FR-β), a collagenous structure (MARCO), and transferrin receptor 1 (TfR1), are found to be overexpressed on the surface of macrophages, which have been employed as biological targets for imaging macrophages in atherosclerotic plaques.…”
Section: Targeted Imaging Of Activated Cells In Atherosclerosismentioning
confidence: 99%
“…WSF-7 upregulated PPARγ-responsive genes, such as adiponectin and Glut4, inhibits PPARγ phosphorylation at Ser273 by obesity and enhances insulin sensitivity in 3T3-L1 Adipocytes ( Zhang et al, 2020 ). Lobeglitazone inhibits the VSMCs proliferation and migration, reduces the vascular cells adhesion, NF-kB p65 translocation, and improves circulating factors related to atherosclerosis, then reduced neointimal formation significantly in balloon injury rat carotid arteries in ApoE –/– mice ( Lim et al, 2015 ; Song et al, 2021 ). In the presence of pro-inflammatory stimulation, Lobeglitazone effectively inhibited expression of pro-inflammatory gene expression in macrophages and adipocytes ( Sohn et al, 2018 ).…”
Section: Selective Pparγ Modulators and Atherosclerosismentioning
confidence: 99%
“…In the presence of pro-inflammatory stimulation, Lobeglitazone effectively inhibited expression of pro-inflammatory gene expression in macrophages and adipocytes ( Sohn et al, 2018 ). The latest study has found that macrophages targeted PPARγ activator Lobeglitazone could rapidly stabilize a coronary artery-sized inflammatory plaque ( Song et al, 2021 ). Both non-clinical and clinical studies have demonstrated that INT131 have the potential to separate insulin-sensitizing actions and undesirable side effects in Patients With Type 2 Diabetes ( DePaoli et al, 2014 ), and it also has the potential to decrease free fatty acids, increase HDL-C ( Dunn et al, 2011 ).…”
Section: Selective Pparγ Modulators and Atherosclerosismentioning
confidence: 99%
“…And then, the inflammation process follows as the decisive phase to combat against bacterial infection and to eliminate damaged cells 3 . During this period, macrophage plays the most important role to present diverse biofunctions such as phagocytosis, promoting inflammation, and producing various cytokines that stimulate new capillary growth, collagen synthesis, and tissue fibrosis 4‐6 . Once the wound is cleaned up by inflammation, the next phase defined as proliferation is demanded for new generated tissues to fill and cover the wound surface 7 .…”
Section: Introductionmentioning
confidence: 99%
“… 3 During this period, macrophage plays the most important role to present diverse biofunctions such as phagocytosis, promoting inflammation, and producing various cytokines that stimulate new capillary growth, collagen synthesis, and tissue fibrosis. 4 , 5 , 6 Once the wound is cleaned up by inflammation, the next phase defined as proliferation is demanded for new generated tissues to fill and cover the wound surface. 7 As the key reparative cell, fibroblast closely correlates with tissue regeneration due to its immigration along the fibrin network.…”
Section: Introductionmentioning
confidence: 99%